2018
DOI: 10.1080/15384101.2018.1520569
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cenp-F localization to nuclear pores and kinetochores

Abstract: In metazoans, the assembly of kinetochores on centrometric chromatin and the dismantling of nuclear pore complexes are processes that have to be tightly coordinated to ensure the proper assembly of the mitotic spindle and a successful mitosis. It is therefore noteworthy that these two macromolecular assemblies share a subset of constituents. One of these multifaceted components is Cenp-F, a protein implicated in cancer and developmental pathologies. During the cell cycle, Cenp-F localizes in multiple cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…However, regardless of the expression of CENPF, the expression of FAK was not changed in the HGC27 cells (Figure 7D ). It was reported that CENPF is mainly located in the nucleus but can enter the cytoplasm in late G2 phase [ 30 , 31 ]. We wondered whether CENPF mediated FAK nuclear export since cytoplasmic FAK could activate the MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, regardless of the expression of CENPF, the expression of FAK was not changed in the HGC27 cells (Figure 7D ). It was reported that CENPF is mainly located in the nucleus but can enter the cytoplasm in late G2 phase [ 30 , 31 ]. We wondered whether CENPF mediated FAK nuclear export since cytoplasmic FAK could activate the MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Further exploration revealed that CENPF could not affect the expression of FAK. Interestingly, we found that CENPF could enter the cytoplasm from the nucleus during G2 phase, and the distribution of FAK in GC cells attracted our attention [ 30 , 31 ]. After the application of PND‐1186, a FAK inhibitor that can retain FAK in the nucleus and inhibit its activity [ 32 ], a molecular mechanism by which CENPF activates the MAPK signaling pathway by promoting FAK entry into the cytoplasm was elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In late anaphase, CENP-F re-localizes to the spindle midzone and the intracellular bridge [118] and is eventually degraded after telophase; this requires two degradation sequences in the protein, particularly involving a region called the box KEN7, and the activity of the APC/C ubiquitin ligase [120]. The ability of CENP-F to interact with different structures is encoded in distinct protein domains (see the map in Figure 1): (i) a microtubule-binding domain, which is crucial to bind mitotic microtubules [121]; (ii) the NudE/EL binding domain, through which CENP-F interacts with dynein/dynactin and localizes the motor proteins at the nuclear envelope at the G2/M transition, via the interaction with the NUP133 nucleoporin (a component of the NUP107-160 subcomplex) [122][123][124], which is a critical localization because dynein is a crucial determinant of the nuclear envelope breakdown, and hence of the timing of mitotic entry; (iii) the kinetochore-binding and CENP-E-binding domains, both essential to localize CENP-F at kinetochores during mitosis [119,125]; (iiii) the C-terminal region of CENP-F, containing both the NLS and the KEN7 box. This domain can also interact with the N-terminal region of the NUP133 nucleoporin, and that interaction is necessary to localize the CENP-F/NUP133 complex at KTs [126].…”
Section: Cenp-fmentioning
confidence: 99%
“…CENPF encodes for Centromeric protein F, a large microtubule regulating protein, dynamically expressed throughout the cell cycle [16]. Depending on the stage of the cell cycle, CENPF localizes in different intracellular sites, including the nuclear envelope and kinetochore, where it has a central role in chromosomal segregation [17,18]. In addition, CENPF localizes at the cilium, both at the sub-distal appendages of the basal body and in the axoneme, and it has a role in cilia biology [15].…”
Section: Introductionmentioning
confidence: 99%